Corporate Entrepreneurship and Strategy Process: A Performance Based Research on Istanbul Market - ÖZDEMİRCİ, ATA (ELSEVIER SCIENCE BV, 2011)
In this study, corporate entrepreneurship which is one of the most important factors of sustainable development process is investigated in the context of strategy process. Corporate entrepreneurship is related with the habits of the company about decision making processes. The decentralization of this process builds an organic structure which the workers can take initiative. This will spread the entrepreneurship process from business owners or leaders to the whole company. The effect of corporate entrepreneurship and different strategy processes on abstract and concrete performance is also examined in this study. The universe of this work is the industrial enterprises of Istanbul which are members of Istanbul Chamber of Industry. The type of the research is hypothetic research. Data collection method is survey. Sample selection method is coincidental.
Keywords: Corporate entrepreneurship; Strategy process; Istanbul; Innovation; Risk taking; Proactiveness; Aggressive competitiveness